The effect of a non-steroidal anti-inflammatory drug on the locomotor activity of reindeer (Rangifer tarandus tarandus) on their natural pastures after clamp castration—a pilot study - Nurmi, Hanna; Hänninen, Laura; Laaksonen, Sauli; Valros, Anna (Acta Veterinaria Scandinavica, 2025)
Abstract Background During seasonal round-ups, free-grazing reindeer are gathered from natural pastures. Reindeer bulls removed from breeding are clamp castrated, traditionally without analgesia, and then returned to the grazing grounds. The new Finnish Animal Welfare Act requires the use of analgesia in painful procedures. Our earlier studies have shown that a single dose of the non-steroidal anti-inflammatory drug (NSAID) meloxicam may maintain therapeutic plasma concentrations for 2–3 days in reindeer. No studies have been conducted on the effect of meloxicam on the locomotor activity of free-ranging castrated reindeer after castration. We installed GPS collars on 16 male reindeer (at least 5 years old, 130–160 kg), chosen to be castrated as a standard procedure during the round-up held on 5 Oct 2020. Of these, eight were randomly selected to receive approximately 0.5 mg/kg of meloxicam subcutaneously (NSAID group) and eight received no analgesia (TRAD group). The trackers were set to provide location twice per hour with 10 m accuracy. From the GPS data, we calculated the daily distances travelled by the reindeer during the 3 days after castration and analysed the differences between the treatments using a GEE model. Fixed factors were treatment (NSAID or TRAD), days (1–3) and hours, and the interactions between these variables. Our key presumption was that a meloxicam injection can reduce the pain related restless locomotion of newly clamp castrated reindeer. Results The overall mean ± SE daily distances travelled by NSAID (n = 8) and TRAD (n = 8) reindeer did not differ (6.60 ± 0.67 km vs. 8.60 ± 1.54 km). However, all reindeer (n = 16) moved more on day 1 than day 3. TRAD reindeer travelled farther than NSAID on day 1 (11.67 ± 2.25 km vs. 7.08 ± 0.61 km, P < 0.05), but no differences were observed on days 2 or 3 due to high variation (10.19 ± 3.87 km vs. 6.59 ± 0.85 km and 5.35 ± 0.39 km vs. 6.17 ± 0.70 m, P > 0.1). NSAID movement remained stable between the days (P > 0.1), while TRAD activity ...